POLA KOMUNIKASI WARTAWAN KOMPAS DALAM SOSIALISASI VAKSINASI COVID-19 - Suf Kasman (Fakultas Dakwah dan Komunikasi, 2021)
This study aims to explain how the Kompas newspapersocializes the Covid-19 immunization in the country. The results of theanalysis of research data processing show that the Kompas newspaperhas a positive and significant effect on the socialization of Covid-19immunization.This is the basis for the government to invite the Kompasnewspaper to take part in carrying out its role as the fourth pillar ofdemocracy to prevent disinformation and broadcast easy-to-understandinformation about the Covid-19 vaccination program.Kompas newspaper has proven to have a major role in providingaccurate information to educate the public. Thanks to the positivesupport of the Kompas newspaper in conveying accurate and reliableinformation, it has become an important key to the success of the Covid-19 vaccination program in the country.